PERANCANGAN ALAT SOLAR DEHIDRATOR BERBASIS IOTSEBAGAI SOLUSI ALTERNATIF UNTUK PROSES PENGERINGANBAHAN PANGAN - Kamdan; Munandar, Rifki Arief; Perkasa, M. Juang Pajri; Ramdan, Hari Muhammad; Kustandi, Agus; Gunawan, Muhamad Sahrul; Yusuf, Maulana; Kharisma, Ivana Lucia; Insany, Gina Purnama (MAJU : Indonesian Journal of Community Empowerment, 2025)
The design of a solar powered dehydrator based on the Internet of Things (IoT) is an alternative solution for the drying process of natural products. This technology aims to optimize drying through measured temperature and humidity control, which is important in maintaining the quality of the dried material. IoT integration enables real-time monitoring and automatic adjustment of drying parameters, ensuring the process remains consistent and eficient. This system can be an innovative solution for small and medium enterprises (SMEs) in the agricultural and herbal sectors, overcoming common challenges in traditional drying methods, such as dependence on weather conditions and uneven drying results. Through trials and testing, this solar dehydrator demonstrated increased ef iciency.